2006
DOI: 10.1042/bj20060843
|View full text |Cite
|
Sign up to set email alerts
|

Invariant Thr244 is essential for the efficient acylation step of the non-phosphorylating glyceraldehyde-3-phosphate dehydrogenase from Streptococcus mutans

Abstract: One of the most striking features of several X-ray structures of CoA-independent ALDHs (aldehyde dehydrogenases) in complex with NAD(P) is the conformational flexibility of the NMN moiety. However, the fact that the rate of the acylation step is high in GAPN (non-phosphorylating glyceraldehyde-3-phosphate dehydrogenase) from Streptococcus mutans implies an optimal positioning of the nicotinamide ring relative to the hemithioacetal intermediate within the ternary GAPN complex to allow an efficient and stereospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…The side chain of invariant Glu-399 was shown to play an essential role in this stabilization by anchoring the NMN ribose through hydrogen bonds with its hydroxyl groups (19). Moreover, recent studies support a critical contribution of the ␤-methyl group of the invariant Thr-244 residue that allows the nicotinamide ring to adopt a productive conformation for hydride transfer (20). Nevertheless, this conformation is not suitable for the deacylation because it would sterically preclude the catalytic Glu-268 from playing its role in the hydrolytic process.…”
Section: Structural Dynamics Associated With Cofactor Binding Have Bementioning
confidence: 93%
“…The side chain of invariant Glu-399 was shown to play an essential role in this stabilization by anchoring the NMN ribose through hydrogen bonds with its hydroxyl groups (19). Moreover, recent studies support a critical contribution of the ␤-methyl group of the invariant Thr-244 residue that allows the nicotinamide ring to adopt a productive conformation for hydride transfer (20). Nevertheless, this conformation is not suitable for the deacylation because it would sterically preclude the catalytic Glu-268 from playing its role in the hydrolytic process.…”
Section: Structural Dynamics Associated With Cofactor Binding Have Bementioning
confidence: 93%
“…Similarly, we have shown that the T244S in human ALDH1A1 resulted in decreased catalytic efficiency and increased K M for NAD + [29]. In both cases, the binding of NADH was only slightly impaired [19,29]. Finally, we have also reported that substitution of Thr-244 reduces catalytic efficiency in human ALDH3A2 as well [30].…”
Section: Introductionmentioning
confidence: 92%
“…1A). The coenzyme NAD(P) + binds to the first Rossmann fold in an unusual manner, where the adenosine occupies a cleft between the αF and αG helices, the pyrophosphates are solvent exposed, and the nicotinamide mononucleotide has been observed to occupy various positions [1619] (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations